Direct Store Delivery Concepts, Applications and Instruments - Otto, Andreas; Schoppengerd, Franz Josef; Shariatmadari, Ramin (Springer Berlin Heidelberg : Imprint: Springer, 2009)
Direct Store Delivery (DSD) is a key method of selling and distributing products for a variety of industries. In the consumer products industry, DSD is one of the strategic key growth areas, as the process delivers a broad range of business benefits to all parties of the value chain. Today, 24 of the world's Top 30 Fast Moving Consumer Goods companies employ the DSD business process. Although DSD is gaining major and steadily increasing attention in the market, it has hardly been covered by literature and empirical studies. For the first time and including the input of both practitioners and academics, this book throws light on the topic of DSD from different perspectives, providing fresh insights and benefits. The book covers diverse topics. Among others, it delivers a deeper understanding of the DSD business process and why companies use it. Furthermore, the global status quo of DSD usage and details of its implementation will be illustrated and multi-level insights (strategic, operational) will be discussed.